How to maximize geometric current density in testing of fuel cell catalysts by using gas diffusion electrode half-cell setups - Schmitt, Nicolai; Schmidt, Mareike; Mueller, Jonathan E.; Schmidt, Lasse; Etzold, Bastian J.M. (Electrochemistry Communications, 2022)
Half-cell gas diffusion electrode (GDE) setups have recently been shown to allow characterization of oxygen reduction reaction (ORR) catalysts at fuel cell relevant current densities and potentials while offering the advantage of fast screening and requiring only minimal sample usage. Most recently, publications suggesting best practices for GDE half-cell characterization have highlighted key challenges in running GDE experiments and have presented measurement protocols that allow excellent Inter-lab comparability. This step can be seen as the cornerstone for broad-based utilization of GDE half-cells. However, what is still missing, is an understanding of what limits the maximum achievable current density in GDE measurements. In this study we highlight the influence of various setup parameters (electrode area, electrolyte concentration, as well as size and position of the counter electrode) on the maximum achievable current density in an automated GDE setup. Furthermore, we present the metrics that need to be considered when adapting the electrochemical protocol for recording ORR polarization curves at higher current densities. The findings observed in this study are not limited to testing the ORR, but can be transferred to any other electrocatalytic reaction tested in a half-cell GDE at high current densities.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Compliance voltage; Fuel cells; Gas diffusion electrode; Oxygen reduction reaction; Pt/C; Setup limitations